Detection of annual rainfall trends using innovative trend analysis method in Benin - KOUGBEAGBEDE, Hilaire (My University, 2024)
The planning and efficient management of water resources are an important subject in any development program. Thus, changes in rainfall patterns are among the major concerns in program design. This study assesses the evolution of rainfall trends on 11 stations that operated from 1922 to 2016. The classic Mann-Kendall method with Sen’s slope and innovative trend analysis method of Şen are applied to annual rainfall at each station. The results show with the Mann-Kendall test that rainfall is decreasing at Bembereke, Natitingou, and Savè, and no change for the rest. With the ITA method, rainfall trends are noticed at ten stations, three are increasing, and seven decreasing. The three increasing stations are Adjohoun, Bopa, and Grand-Popo. The only station with no trend is Abomey. With the graphical analysis proposed by the ITA method, the low, medium, and high classes show trends that vary from one station to another.
Keywords: climate change; trend; innovative trend analysis; rainfall; Benin; Mann-Kendall.